Sex Selection in the United Kingdom - McMillan, John (The Hastings Center report, 2002)
The British have taken a comprehensive approach to regulating reproductive medicine. A loophole in the current law leaves some cases of sex selection uncovered; if that loophole were closed, however, the law is robust enough to address the concerns about sex selection while permitting it in many cases.